Cash Flow Analysis and Management of Project Portfolio Using Percentile Points (International Journal of Innovative Research in Engineering & Management, 2023)
Effective financial and cash flow  management are essential elements of an effective project  execution plan. For this study, five projects were being  executed simultaneously by SOFTSTRUCT  CONSULTANTS, a construction company based in Port  Harcourt, Nigeria. The company has an overdraft limit of  $1,200,000. They are to commence on different dates  starting from September 2022 and ending at February 2026.  The percentile point (PP) method was used to generate the  cash flow analysis and management. It was found that the  company arrived at a maximum overdraft of $1,200,000,  which was less than the limit. This means the company is  on the safe side to succeed with her project portfolio, and  likely remain afloat to execute more projects in the future,  using this kind of cash flow management technique for all  her projects.
Keywords: Cash Flow; Financial Management; Percentile Points; Project Portfolio Management